PROFESSIONAL ORIENTATION OF TEACHING MATHEMATICS AT SCHOOL (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
The article shows the professional orientation of teaching mathematics at school, solving practical problems related to the knowledge of some specific mathematical models from the field of economics, the ability to translate conditions formulated in the form of a text into equations and inequalities.